Estrogen receptor and temperature independently influence sex determination in the red-eared slider turtle - Xifeng Wang; Zihan Ding; Zihan Ding; Pengfei Wu; Jiong Fu; Weiguo Du; Weiguo Du (Frontiers in Endocrinology, 2025)
In reptiles with temperature-dependent sex determination (TSD), including the red-eared slider turtle Trachemys scripta elegans, female sex determination is sensitive to estrogen. However, the underlying molecular mechanism by which estrogen facilitates ovarian development remains unclear in TSD. Here, we explore the role of estrogen receptors (ESRs) in ovarian differentiation by administering 17β-estradiol (E2), as well as agonists and antagonists of ESRs to embryos of red-eared sliders. We found that treatment with E2 or one of the ESR (ESRα, ESRβ, or GPER1) agonists induced typical female characteristics of gonads at the male-producing temperature (MPT), exhibiting advanced outer cortex and degraded medullary cord as well as upregulation of Cyp19a1 and Foxl2 and downregulation of Amh and Dmrt1. In addition, this male-to-female sex reversal induced by E2 at MPT can be reversed by using a combination of three ESR antagonists. However, antagonizing any of the three ESRs or the three ESRs together did not affect ovarian differentiation at the female-producing temperature (FPT). Our study demonstrates that estrogen regulates the expression of estrogen-responsive sex-specific genes through the ESRs to induce ovarian differentiation at MPT, and ESRs do not have to engage in ovarian development directly at FPT, indicating that alternative pathways might drive feminization under natural high-temperature conditions.